Antiviral IgM and IgG subclasses in varicella zoster associated neurological syndromes. Issue 5 (May 1989) - Mathiesen, T; Linde, A; Olding-Stenkvist, E; Wahren, B
Abstract : The varicella zoster virus (VZV) and herpes simplex virus (HSV) IgGl-4 subclasses were compared in serum and cerebrospinal fluid (CSF) of 22 patients with VZV-associated neurological symptoms, 12 patients with HSV-associated neurological symptoms and 14 controls. The clinical syndromes of the VZV-associated diseases comprised meningo-encephalitis, myelitis, myelopathies and polyneuropathies, mostly with a favourable outcome. A characteristic finding was an intrathecal synthesis of VZV IgG1 and HSV-3. Commonly also IgG2 and 4 were seen in CSF of VZV patients. Their intrathecally synthesised HSV IgG was restricted to IgG1. VZV IgG3 occurred in serum and/or CFS together with VZV IgM in 14 cases and may be a marker of recent VZV replication. In patients with HSV-associated neurological disease, a multi-IgG subclass HSV response and concomitant VZV antibodies restricted to IgG1 was found. Intrathecal synthesis of both HSV and VZV IgG occurred in 20 patients. Detection of two or more VZV or HSV specific IgG subclasses synthesised intrathecally identified the aetiological agent in 19 of these 20 cases.